Microbiological changes occurring in trout fillets (Oncorhynchus mykiss W. 1792) salted and treated with potassium sorbate during production and storage - Öksüztepe, Gülsüm; Inanli, Ayşe Gürel (Asian Network for Scientific Information, 2007)
In this study, microbiological changes during processing and storage of salted-cured trout fillets treated with potassium sorbate were investigated. For this purpose, 10 and 15% (w/w) NaCl and 1, 5 and 10% (w/v) potassium sorbate were applied to the fillets. The processed fillets were vacuum-packed and storage at 4°C. The samples were analyzed in some periods of production and in the storage days of 7, 14, 28, 42, 56, 70 and 84 for numbers of total mesophilic aerob, psycrophylic, yeast and mould. In conclusion, the microbiological quality of all samples treated with 15% NaCl and potassium sorbate were found better. Consequently, it can be concluded that the usage of potassium sorbate may be useful and a synergistic effect between salt and potassium sorbate determined. © 2007 Asian Network for Scientific Information.
Keywords: Microbiological; Potassium sorbate; Quality; Rainbow trout (Oncorhyncus mykiss W.); Salted fish